Left ventricular mass and systolic function in children with chronic kidney disease: comparing echocardiography with cardiac magnetic resonance imaging - Arnold, Raoul; Schwendinger, Daniel; Jung, Sabine; Pohl, Martin; Jung, Bernd; Geiger, Julia; Gimpel, Charlotte (Pediatric nephrology, 2016)
Increased left ventricular mass (LVM) is an important risk marker of uremic cardiovascular disease. Calculation of LVM by echocardiography (Echo) relies on geometric assumptions and in adults on hemodialysis overestimates LVM compared to cardiac magnetic resonance (CMR). We compare both techniques in children with chronic kidney disease (CKD).